Finance-based accounting of coal emissions. (24th March 2021) - Manych, Niccolò; Steckel, Jan Christoph; Jakob, Michael
Abstract: Most new coal-fired power plants are currently being constructed in Asia. These plants are financed by banks and investors, which in many instances reside elsewhere. This paper examines the international dimension of coal financing from commercial banks and institutional investors based on a newly constructed dataset. We analyse domestic as well as cross-border financial flows and propose a methodology to calculate 'finance-based emissions' associated with the construction of coal-fired power plants. Our results indicate that financial institutions from the United States, Europe and Japan play a major role in financing coal plants globally, especially in terms of loans, bonds and equity investment. From a finance-based perspective some countries account for a substantially larger share of coal emissions than under the commonly used territorial approach that assigns emissions to the country where they are released.